Effect of Training, Work Facilities and Organizational Climate on the Performance of Health Workers at Cahaya Bunda Mother and Child Hospital - Rismala Karnan; Ellin Herlina; Bambang Sumardi (PT. Berkah Digital Teknologi, 2023)
Purpose of the study — This study aims to determine: How much influence the training, work facilities, and organizational climate simultaneously on the performance of health workers at the Cahaya Bunda Hospital, Cirebon, both partially and simultaneously. Research site at the Cahaya Bunda Hospital for Mothers and Children, Cirebon CityResearch method—The population of health workers at the Cahaya Bunda Mother and Child Hospital, Cirebon City, amounted to 240 people, a sample of 70 people. Design This study uses a quantitative approach. Quantitative approach, survey method, this type of research is causal associative research with data analysis technique using Multiple Linear Regression analysisResult— The results of this study indicate: 1) There is a positive and significant influence partially partially on the performance of health workers at the Cahaya Bunda Hospital, Cirebon City. The magnitude of the positive effect of training on the performance of health workers is 82.6% while the remaining 17.4% is influenced by other factors. 2) There is a positive and significant effect of working facilities partially on the performance of health workers at the Cahaya Bunda Hospital, Cirebon City. The magnitude of the influence of work facilities on the performance of health workers is 4.9% while the remaining 95.1% is influenced by other factors. 3) There is a partial positive and significant influence of organizational climate on the performance of health workers at the Cahaya Bunda Hospital, Cirebon City. The magnitude of the influence of Organizational Climate on the Performance of Health Workers is 17.8% while the remaining 82.2% is influenced by other factors. 4) There is a positive and significant effect of training, work facilities, and organizational climate simultaneously on the performance of health workers at the Cahaya Bunda Hospital, Cirebon City. The magnitude of the influence of training, work facilities, organizational climate on the performance of health workers is 97.4% while the remaining 2.6% is influenced by other factorsConclusion— This study concludes that training, work facilities, and organizational climate have a significant positive impact on the performance of health workers at Cahaya Bunda Mother and Child Hospital in Cirebon City. Adequate training programs contribute significantly to performance, while the availability of proper work facilities and a positive organizational climate also play important roles. Addressing these factors collectively can greatly enhance the performance of health workers. The practical implication is that investing in training, improving work facilities, and fostering a positive work environment are essential for optimizing health worker performance. This, in turn, can lead to improved healthcare outcomes and satisfaction for both patients and healthcare providers.